Pola Kepemimpinan Ketua Kwartir Daerah Kepanduan Hizbul Wathan Kota Yogyakarta Tahun 2017-2019 dalam Membentuk Kader Militansi Organisasi - Fandi Akhmad; Fadhlurrahman Fadhlurrahman (MODELING: Jurnal Program Studi PGMI, 2023)
Leadership in an organization is needed, because a leader has an effort to move people in this matter under him, in achieving certain goals that have been set, including in the leadership of Hizbul Wathan. After the emergence of the Hizbul Wathan Scouting Movement in 1960 which was signed by the Central Executive of Muhammadiyah at that time Buya Syafii Maarif made the cadres of the Muhammadiyah organization who had a guiding spirit rise and immediately spread in a structured diaspora to establish the Hizbul Wathan Scouting Movement in their respective regions, Yogyakarta was no exception. which became the forerunner to the center of the scouting movement of Hizbul Wathan. In the city Yogyakarta has also experienced ups and downs of the Hizbul Wathan scouting movement which has the slogan "talk less, work more". However, from 2017 to 2019 the leadership of the Kwartir Regional Scouting Region of Hizbul Wathan rose again to show its existence, which was led by Ramanda Hendri with six division heads who had members under them divided into each division according to their respective abilities. However, after the fall of the leadership period of Ramanda Hendri, the Kwartir Regional Scouting Hizbul Wathan in the city of Yogyakarta experienced a decline in quality marked by a marked lack of activity, and the departure of members under it. The purpose of this study was to determine the pattern of leadership of the Hizbul Scout Kwartir Region Wathan Kota Yogyakarta in 2017-2019 in shaping the character of deep militancy organize. The method in this research uses descriptive qualitative research based on case studies. Meanwhile, to analyze the descriptive data in this study by sorting the data to interpret the findings in the field, then the process of source triangulation was carried out. The Leaders of the Hizbul Wathan Scouting Regional Kwartir in the City of Yogyakarta in 2017-2019 strive to realize quality Hizbul Wathan scouting from scouting abilities and good morals towards others. In addition, it also determines a comprehensive pattern of cadre development for each board. Implementation of resource management to improve ability to complete work programs in each field. and strengthening the spirit of struggle by encouraging its members to take part in the cadre formation stages.